2019
DOI: 10.3906/tar-1807-15
|View full text |Cite
|
Sign up to set email alerts
|

Precision cane meristem management can influence productivity and fruit quality of floricane red raspberry cultivars

Abstract: Introduction Horticulture plants have been recognized for their human health benefits. They have a high content of nonnutritive, nutritive, and bioactive compounds, such as flavonoids, phenolics, anthocyanins, phenolic acids, and as well as nutritive compounds, such as sugars, essential oils, carotenoids, vitamins, and minerals. Bioactive compounds from horticulture plants have potent antioxidant, anticancer, and antimutagenic, etc., properties (Ercisli et al., 2003; Dogan et al., 2014; Alp et al., 2016). Rasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Thusly, in previous studies, differences in cultivars were put forth with principal component analysis in walnuts [42,[59][60][61], kiwifruit [62], strawberry tree [63], hazelnuts [33], almonds [35], raspberry [64], citrus [65] and apricot [66]. All above studies indicated that PCA allows the extraction of the maximum information from used cultivars and underlining the interrelations between variables and individuals, either by similarity or opposition.…”
Section: Eigen Statistics For Two Principal Componentsmentioning
confidence: 99%
“…Thusly, in previous studies, differences in cultivars were put forth with principal component analysis in walnuts [42,[59][60][61], kiwifruit [62], strawberry tree [63], hazelnuts [33], almonds [35], raspberry [64], citrus [65] and apricot [66]. All above studies indicated that PCA allows the extraction of the maximum information from used cultivars and underlining the interrelations between variables and individuals, either by similarity or opposition.…”
Section: Eigen Statistics For Two Principal Componentsmentioning
confidence: 99%
“…Fruit species play a critical role in maintaining the global biodiversity and are essential to all living beings. Research on temperate fruit crops necessitates the fusion of fundamental and practical elements of plant physiology, ecosystem and genetics ( Eyduran et al, 2015 ; Životić et al, 2019 ). The almond ( Prunus dulcis [Mill.]…”
Section: Introductionmentioning
confidence: 99%
“…Its berries are large, bright red, firm, aromatic and of good transportability. It is particularly sensitive to Phytophthora root rot and has low tolerance to winter injury (Stojanov et al, 2019;Životić et al, 2019).…”
Section: Introductionmentioning
confidence: 99%